Coffee and tea consumption and cardiovascular disease and all-cause and cause-specific mortality in individuals with diabetes mellitus: a meta-analysis of prospective observational studies - Ding, Li; Wang, Hai-Peng; Zhao, Jun-Yu; Zhao, Xin; Sha, Yu; Qin, Li-Qiang; Hidayat, Khemayanto (Frontiers in Nutrition, 2025)
BackgroundIndividuals with diabetes mellitus (DM) are more likely to develop cardiovascular disease (CVD) and die prematurely than those without this condition. Coffee or tea consumption has been linked with lower risks of developing CVD and premature death in general populations. A meta-analysis of published prospective observational studies was performed to provide up-to-date evidence on the association between tea or coffee consumption and the risks of CVD and all-cause and cause-specific mortality in individuals with DM.MethodsThe PubMed, Web of Science, Cochrane Library and Embase databases were searched. A Random-effects model was used to estimate the pooled hazard ratios (HRs) and 95% confidence intervals (CIs).ResultsCompared with the lowest consumption category, the highest coffee consumption was associated with lower risks of all-cause mortality (HR 0.82, 95%CI 0.73, 0.91; n = 9), coronary heart disease (CHD) mortality (HR = 0.66, 95% CI: 0.51, 0.85; n = 3), CVD incidence (HR = 0.85, 95% CI: 0.75, 0.97; n = 2), and CHD incidence (HR = 0.82, 95% CI: 0.68, 0.99; n = 3). Similarly, the highest tea consumption was associated with lower risks of all-cause mortality (HR = 0.85, 95%CI: 0.79, 0.92; n = 6) and CVD mortality (HR = 0.86, 95% CI: 0.80, 0.93; n = 5). Linear associations were observed between coffee consumption and the risks of CVD mortality, CHD mortality, CVD incidence, and CHD incidence, as well as between tea consumption and the risk of CVD mortality. Nonlinear associations were found between coffee or tea consumption with the risk of all-cause mortality, with the greatest risk reduction observed at one to four cups of coffee per day or up to two cups of tea per day. The certainty of the evidence was mostly graded as moderate for coffee consumption (except for cancer mortality and stroke incidence, which were graded as low) and low for tea consumption (except for CVD mortality, which was graded as moderate).ConclusionDaily coffee or tea consumption may be associated with lower risks of CVD and death, particularly from CVD, among individuals with DM. However, However, due to the observational design, methodological limitations, and low to moderate certainty, these findings should be interpreted cautiously.